Willingness to Pay Masyarakat Terhadap Pengolahan Sampah Ramah Lingkungan di TPA Dusun Toisapu Kota Ambon - Angela Ruban; Eka Intan Kumala Putri; Meti Ekayani (Departemen Ekonomi Sumberdaya dan Lingkungan, Fakultas Ekonomi dan Manajemen, Institut Pertanian Bogor, 2014)
Toisapu Village Landfills in Ambon has been established since 2003 using open dumping system in processing the waste. These activity has caused negative externalities for the people living around the landfill. This paper aimed to analyze the factors that affected people's willingness to pay a higher levy for better waste management, the amount of the retribution to pay, and the closure of the operational costs through the analysis of willingness to pay (WTP) with four scenarios offered in the Baguala and Nusaniwe Regencies. The results showed that the factors affecting people's willingness to pay a higher retribution in the Baguala and Nusaniwe regencies were the level of education and the distance between their home and landfill. The highest average of WTP in Baguala regency of biogas scenario was Rp 24.250/ KK/ month, and the lowest in the incineration scenario was Rp 20 804/ KK /month. While in the Nusaniwe regency, the highest average of WTP obtained was Rp 21 228/ KK/ month in composting scenario, and the lowest was of Rp 18 220/ KK/ month in sanitary landfill scenario. The value of society WTP obtained was the value of retribution to pay, and this value could cover the operational costs required to implement the four scenarios of waste management offered.